Invited Commentary: Built Environment and Obesity Among Older Adults—Can Neighborhood-level Policy Interventions Make a Difference? - Michael, Yvonne L. (Oxford University Press, 2009)
Obesity is more prevalent and its consequences severe among middle-aged and older adults. Efforts to understand and address neighborhood-level causes of obesity in this population offer the potential to enhance health and reduce the costs of obesity for everyone. The accompanying paper by Li et al. (Am J Epidemiol. 2009;169(4):401–408) presents new data on the apparently significant interaction between neighborhood and individual characteristics on 1-year change in body weight and waist circumference. Despite methodological limitations in measurement, this paper supports the importance of future research that considers the complex relation between people and where they live. Efforts to design neighborhood-level policy interventions to effectively address the problem of obesity will require greater interdisciplinary collaboration.